Penguasaan Konsep dan Keterampilan Berpikir Kritis Melalui Pembelajaran PODE Materi Sistem Pencernaan Menggunakan Zoom Meeting - Aghisni, Ulhaq; Jayadinata, Asep Kurnia; Sudin, Ali (Jurnal Pena Ilmiah, 2021)
Science is a teaching material that discusses phenomena in daily life because the learning process always involves science because what it learns is about natural events. The process to find explanations about natural events that occur in the environment, of course, requires good thinking skills about concepts and thinking critically as needed in the 21st century. In learning, teachers must be able to design science learning that makes it easier for students to have a good understanding and be sensitive to the environment that can be useful for students in solving problems in everyday life. This study uses a descriptive method with a qualitative approach. The result can be said to have been carried out well by teachers and students. After the learning implementation, the mastery of the concept by the student's critical thinking skills, in general, can be shown to be good.